Systematic quantitative analysis of ribosome inventory during nutrient stress - An, Heeseon; Ordureau, Alban; Körner, Maria; Paulo, Joao A.; Harper, J. Wade (Nature (London), 2020)
Mammalian cells reorganize their proteomes in response to nutrient stress through translational suppression and degradative mechanisms using the proteasome and autophagy systems 1 , 2 . Ribosomes are central targets of this response, as they are responsible for translation and subject to lysosomal turnover during nutrient stress 3 – 5 . The abundance of ribosomal (r)-proteins (around 6% of the proteome; 10 7 copies per cell) 6 , 7 and their high arginine and lysine content has led to the hypothesis that they are selectively used as a source of basic amino acids during nutrient stress through autophagy 4 , 7 . However, the relative contributions of translational and degradative mechanisms to the control of r-protein abundance during acute stress responses is poorly understood, as is the extent to which r-proteins are used to generate amino acids when specific building blocks are limited 7 . Here, we integrate quantitative global translatome and degradome proteomics 8 with genetically encoded Ribo–Keima 5 and Ribo–Halo reporters to interrogate r-protein homeostasis with and without active autophagy. In conditions of acute nutrient stress, cells strongly suppress the translation of r-proteins, but, notably, r-protein degradation occurs largely through non-autophagic pathways. Simultaneously, the decrease in r-protein abundance is compensated for by a reduced dilution of pre-existing ribosomes and a reduction in cell volume, thereby maintaining the density of ribosomes within single cells. Withdrawal of basic or hydrophobic amino acids induces translational repression without differential induction of ribophagy, indicating that ribophagy is not used to selectively produce basic amino acids during acute nutrient stress. We present a quantitative framework that describes the contributions of biosynthetic and degradative mechanisms to r-protein abundance and proteome remodelling in conditions of nutrient stress. During nutrient stress, ribosomal protein abundance is regulated primarily by translational and non-autophagic degradative mechanisms, but ribosome density per cell is largely maintained by reductions in cell volume and rates of cell division.